2017
DOI: 10.1016/j.genhosppsych.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a randomized exercise trial on physical activity, psychological distress and quality of life in older adults

Abstract: Objective Evidence suggests improvements in positive psychological health indices (e.g., self-esteem) may explain the relationship between physical activity and quality of life (QoL) in older adults. Less is known about the role of reductions in negative psychological health indices (e.g., depression). The present study examined the effects of changes in moderate-to-vigorous physical activity (MVPA) and psychological distress on change in QoL in older adults enrolled in an exercise program. Methods Older adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
77
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 62 publications
9
77
0
8
Order By: Relevance
“…Thus, a decrease in the intensity of depressive symptoms in female UTA students is by all means a positive change. Also, results of previous investigations prove that regular leisure time physical activity in older age produces strong and long-term antidepressant effects and considerably reduces susceptibility to stress [4,20,[22][23][24][25][26]. The findings of the present study are in line with the outcomes of earlier studies -participation of elderly persons in regular physical activity led to a decrease in depression levels and an increase in self-rated health [14,21].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, a decrease in the intensity of depressive symptoms in female UTA students is by all means a positive change. Also, results of previous investigations prove that regular leisure time physical activity in older age produces strong and long-term antidepressant effects and considerably reduces susceptibility to stress [4,20,[22][23][24][25][26]. The findings of the present study are in line with the outcomes of earlier studies -participation of elderly persons in regular physical activity led to a decrease in depression levels and an increase in self-rated health [14,21].…”
Section: Discussionsupporting
confidence: 91%
“…A 12-week programme of aerobic exercises for ageing adults already produced positive outcomes regarding quality of life [12,14]. Moderate physical activity may bring about an improvement in perceived life quality and a reduction in the incidence of risk factors related to depression disorders [4]. Within a period of one month, physically active senior citizens have an average of 14 'unhealthy days' less than their physically inactive peers (self-rated physical and psychological health).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engagement in regular PA such as walking, cycling, work-related activity, sports, gym work, dancing or gardening has been associated with a reduction in the risk of development, or progression, of cardiovascular and cerebrovascular disease, type II diabetes, cognitive decline, obesity, falls and fractures [46]. Other benefits of regular physical activity include a greater sense of well-being and self-esteem [7]. …”
Section: Introductionmentioning
confidence: 99%
“…According to WHO (World Health Organization 2015, accessed on 15/02/19), people over the age of 65 who engage in a high level of physical activity experience a lower overall mortality, while at the same time improve functional health. It has been found that physical activity in older people has a positive effect, on not only their cognitive and physical function, but it also helps to reduce stress and therefore promote a higher quality of life (Awick et al 2017). Evidence has shown that a lack of physical activity is a major risk factor for a higher rate in mortality, disease and disability (Physical Activity Guidelines 2018).…”
Section: Introductionmentioning
confidence: 99%